(untitled) (Editora Impacto Científico, 2025)
The Peruvian Amazon region faces increasing pressures stemming from extractivism, deforestation, and climate change, a context in which Indigenous and rural women have emerged as key actors in territorial defense and biodiversity conservation. This study aimed to examine the experiences, strategies, and challenges of women’s community leadership in the Peruvian Amazon through a scoping review. The methodological framework of Arksey and O’Malley (2005) was followed, with searches conducted in Scopus, Web of Science, SciELO, Redalyc, and Google Scholar, as well as institutional reports, for the period 2010–2025. From an initial 142 records, 32 documents were selected for full analysis. The results reveal three main findings: first, women exercise leadership through community-based organizations, interethnic networks such as ONAMIAP, and strategies that include community education, documentation of ancestral knowledge, and legal mobilization; Second, significant achievements were identified, such as the approval of the Prior Consultation Protocol with a gender perspective (2021), conservation projects like the "Women’s Forest," and international recognition. Third, structural challenges persist, including gender-based violence (68% report harassment), political exclusion (only 12% hold leadership positions), lack of sustainable funding, and multiple domestic responsibilities. It is concluded that Amazonian women’s leadership constitutes a transformative force based on principles of reciprocity, spirituality, and a relationship with nature, and its strengthening is a necessary condition for the socio-environmental sustainability of the region. DOI: https://doi.org/10.56238/edimpacto2025.090-055